PENGARUH PENDIDIKAN KESEHATAN METODE DEMONSTRASI TERHADAP HAND HYGIENE 6 LANGKAH 5 MOMEN KELUARGA PASIEN - Binti Rosidah (Media Husada Journal Of Nursing Science, 2022)
Hospital arrangement is a place that has a high risk of Healthcare Associated Infection (HAIs). Family behavior and patients undergoing treatment at the hospital greatly influence the emergence of HAIs, one of which is applying handwashing. Health education is one way to improve the accuracy of hand washing 6 steps the first moment. The purpose of this study was to determine the difference in the accuracy of the implementation of hand washing in the patient's family with and without the provision of health education using the hand hygiene demonstration method in Irna 2 Surgery Room, RSUD Dr. Saiful Anwar Malang. Method: The design of this study was a quasi-experimental study with a non-equivalent control group design. The treatment group was given an intervention in the form of demonstration method handwashing education, while the control group was not given an intervention. 26 respondents as the control group and 26 respondents as the treatment group. Result and analysis: The results obtained 14 respondents (53.85%) in the control group did not wash their hands properly. 17 respondents (65.38%) in the intervention group washed their hands properly. There is a difference in the accuracy of hand washing in the patient's family in IRNA 2 Surgical Class 3 of RSUD Dr. Saiful Anwar Malang between control and intervention groups (p<0.05). Health education demonstration method increases the accuracy of handwashing in the patient's family. It is hoped that education about 6 steps of hand washing will continue.